2023
DOI: 10.1097/prs.0000000000010201
|View full text |Cite
|
Sign up to set email alerts
|

Use of High-resolution Ultrasound in Characterizing a Breast Implant and Detecting a Rupture of the Device Before Reoperation in Women Receiving Augmentation Mammaplasty

Abstract: Summary: With the emergence of state-of-the art implant technology and advanced surgical techniques, plastic surgeons face challenging problems, such as identification of a specific type of a device and diagnosis of postoperative complications, in managing patients undergoing implant-based augmentation mammaplasty. In this article, the authors introduce a novel method for characterizing a breast implant based on diverse factors (eg, filler properties, type of pocket, surface topography, shape type, and manufac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(31 reference statements)
0
3
1
Order By: Relevance
“…An annual breast implant examination is recommended for patients to prevent the exacerbation of silicone migration to regional lymph nodes or adjacent tissue, which could prompt non-radical silicone removal and unnecessary lymph node biopsies. While it has been reported that patients with current extracapsular ruptures may commonly present with symptoms [21], our study found that approximately 90% of patients with snowstorm signs in ultrasonography, with or without silicone invasion to adjacent tissue or lymph nodes, were asymptomatic. This suggests that extracapsular ruptures may be overlooked, underscoring the importance of regular follow-up for early diagnosis.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…An annual breast implant examination is recommended for patients to prevent the exacerbation of silicone migration to regional lymph nodes or adjacent tissue, which could prompt non-radical silicone removal and unnecessary lymph node biopsies. While it has been reported that patients with current extracapsular ruptures may commonly present with symptoms [21], our study found that approximately 90% of patients with snowstorm signs in ultrasonography, with or without silicone invasion to adjacent tissue or lymph nodes, were asymptomatic. This suggests that extracapsular ruptures may be overlooked, underscoring the importance of regular follow-up for early diagnosis.…”
Section: Discussioncontrasting
confidence: 72%
“…Several studies have compared the diagnostic accuracy of mammography, ultrasound, and MRI in detecting implant ruptures [13][14][15][16][17]. Recently, high-resolution ultrasonography (HRUS) has emerged as a valuable tool for diagnosing implant-related complications, including ruptures, and has demonstrated efficacy in identifying device types and manufacturers [9,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Mammograms and MRI, which are used to monitor breast implant-related complications, cannot identify the implant shell surface topography. Only ultrasonography can identify the inserted implant shell surface topography [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Its 3-year safety has been recently assessed using high-resolution ultrasound (HRUS) [ 24 ]. Indeed, the importance of the use of HRUS in assessing the safety of SGBIs has been well documented in the literature [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 51 , 52 ]. Along the continuum of these previous studies, we have efficiently used three-dimensional (3-D) simulation technology and HRUS to maximize both the aesthetic outcomes and safety of the Motiva Ergonomix TM Round SilkSurface.…”
Section: Introductionmentioning
confidence: 99%